SHOPPE GAMES: HOW SHOPPE UTILIZES GAMIFICATION TO INCREASE APP UPTIME - Nurjulya Ningsih; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study examines how Shopee leverages gamification to increase user engagement, particularly by enhancing the time spent on its application. The research employs a qualitative approach with a literature review method, analyzing relevant studies on gamification in e-commerce. Findings reveal that gamification elements such as rewards, challenges, and social interaction significantly contribute to prolonged app usage. Rewards motivate users with tangible incentives, challenges create engaging experiences through progressively difficult tasks, and social interaction fosters connections through competition and collaboration. These results align with Self-Determination Theory and Flow Theory, which emphasize the role of fulfilling psychological needs and creating immersive experiences in driving engagement. The study provides practical insights for app developers, highlighting the importance of designing effective gamification strategies to enhance user retention and loyalty. However, limitations include the absence of primary empirical data, suggesting future research should explore the direct impact of gamification on diverse user demographics through quantitative or mixed-method approaches.